2023
DOI: 10.3390/pharmaceutics15051342
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Production of Biopharmaceuticals via Microwave-Assisted Freeze-Drying (MFD)

Abstract: Recently, attention has been drawn to microwave-assisted freeze-drying (MFD), as it drastically reduces the typically long drying times of biopharmaceuticals in conventional freeze-drying (CFD). Nevertheless, previously described prototype machines lack important attributes such as in-chamber freezing and stoppering, not allowing for the performance of representative vial freeze-drying processes. In this study, we present a new technical MFD setup, designed with GMP processes in mind. It is based on a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
0
8
1
Order By: Relevance
“…However, the relationship between microwave-assisted freeze-drying processes and protein concentrations remains unclear. Recent studies have demonstrated that increasing the solute concentrations of stabilizers, such as sucrose and trehalose, results in enhanced dielectric heating [ 13 , 17 ]. To further investigate the effect of protein concentration in microwave-assisted drying processes, we gradually substituted sucrose with mAb (F1–F4, Table 1 ) and applied drying process P1 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the relationship between microwave-assisted freeze-drying processes and protein concentrations remains unclear. Recent studies have demonstrated that increasing the solute concentrations of stabilizers, such as sucrose and trehalose, results in enhanced dielectric heating [ 13 , 17 ]. To further investigate the effect of protein concentration in microwave-assisted drying processes, we gradually substituted sucrose with mAb (F1–F4, Table 1 ) and applied drying process P1 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reviews have been provided on the rational design of robust and optimized freeze-drying processes [ 4 , 5 , 6 , 7 ], as well as ideas for speeding up the typically lengthy process [ 8 , 9 , 10 , 11 ]. More recently, microwave-assisted freeze-drying (MFD) has gained attention due to its potential for significant time savings while maintaining the product quality of probiotics [ 12 ], vaccines, and proteins [ 13 , 14 ] and, more specifically, monoclonal antibodies (mAbs) [ 15 , 16 , 17 ]. While heat transfer in conventional freeze-drying (CFD) is primarily limited to convection, with some conduction and radiation, microwaves directly interact with the dipolar molecules of the formulation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations